'I'll do it by myself as I knew it all along': On the failure of hindsight-biased principals to delegate optimally - David Danz; Frank Hüber; Dorothea Kübler; Lydia Mechtenberg; Julia Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
With the help of a simple model, we show that the hindsight bias can lead to inefficient delegation decisions. This prediction is tested experimentally. In an online experiment that was conducted during the FIFA World Cup 2010 participants were asked to predict a number of outcomes of the ongoing World Cup and had to recall their assessments after the outcomes had been realized. This served as a measure of the hindsight bias for each participant. The participants also had to make choices in a delegation game. Our data confirm that hindsight-biased subjects more frequently fail to delegate optimally than subjects whom we have classified as not hindsight biased.
Keywords: C72; C91; D84; 330; hindsight bias; delegation; experiments